THE SECOND REVIEW REQUESTING CONTROVERS IN CRIMINAL CASES - Chairul Huda (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
Formally, the review can be carried out more than once, based on the Decision of the Constitutional Court (MK) No. 34/PUU-XI/2013, which states that Article 268 paragraph (3) of the Criminal Procedure Code is contrary to the 1945 Constitution of the Republic of Indonesia and therefore has no binding force as law. This paper intends to discuss the second review's philosophical, juridical, and sociological aspects. The Supreme Court, through SEMA No. 10 of 2009 as strengthened by SEMA No. 7 of 2014, confirms that a review of more than one time is only possible if there is an object of the case there are 2 (two) or more judicial review decisions that conflict one another. The restriction on review from being submitted only once is intended to provide justice to the victim, the community, and the state. The extraordinary effort remains within a measurable corridor and does not limit access to justice for the convict.